Kinematic models of «Ground antenna — space vehicle» mechanical system - Лабуткина, Татьяна Викторовна; Петренко, Александр Николаевич (Technology audit and production reserves, 2013)
The method of analysis of possible motion variants of space vehicles of the satellite system within the view of its ground stations is suggested. It is meant to be used at the stage of satellite systems design. The method is based on two simplified kinematic models of mechanical system «ground antenna — space vehicle» (the models, describing the kinematics of the line connecting the location point of an integrated station of the satellite system with the center of space vehicle masses as it moves above the local horizon of the ground station). In the models, the kinematic parameters of mechanical system (angles, directing the ground antenna to the space vehicle and the distance between the ground station and the space vehicle) are expressed not as a temporal function, but as a function of an introduced universal parameter. The first model does not take into account the Earth’s rotation that allows using merely analytical correlations. The second (specified) model takes account of the Earth’s rotation, and the rotation time is expressed as the function of the introduced universal parameter. The use of the proposed method allows prompt analysis of parameters of connection between ground antennas and space vehicles, estimating not only maximum and minimal values, but getting average values as well by conducting qualitative analysis on the set of possible visibility intervals of space vehicles of the satellite system.